Applicability of ICT-supported language teaching in contexts of social integration and international cooperation - García Alonso, Juan Luis; Samy, Doaa (Círculo de Lingüística Aplicada a la Comunicación, 2018)
This paper offers two examples of the applicability of ICT-supported language teaching in two different contexts: social integration and international cooperation. A search for methodologically innovative approaches in this field inspires a series of collaborative international projects involving Egypt and several European countries. The introduction of best practices in this field brings an improvement in the language teaching and learning process in Egyptian universities, as well as meaningful insights on the advantages and shortcomings of the different options available. ICT facilitates the creation of open access materials available to disadvantaged groups (refugees or immigrants) that are outside conventional educational contexts but need tools and resources for a fast acquisition of foreign languages. An example of these tools is the development of a new multilingual smartphone app based on communication needs. The app is currently being developed within an international consortium including 6 European and 6 Egyptian universities. Another example of interesting use of ICT-based methodologies is the MOOC-based teaching and learning of languages at Cairo University, an experience resulting from the collaboration with the European Universities that are partners in different international projects.